ORGANISM’S MAIN REACTIVE POTENTAL SPECIALITIES OF YOUNG CHILDREN BY BCG-LYMPHADENITIS - Bobrovytska, A.I.; Holubova, T.F.; Sukhodolska, V.V. (Інфекційні хвороби, 2015)
One of the actual problems for nowadays is tuberculosis’ sickness and death rate. Ukraine as well as other CIS countries is the countries with high rate of tuberculosis sickness – indicator for 100 k populations is more than 30 cases. The most difficult situation for tuberculosis is in Southeast Ukraine region. In period of years 2005-2013 total sickness rate was between 84,1 (2005 y.) and 70,9 (2013 y.) for 100k population, death rate – 25,3 and 18, 0 accordingly. Among children of age 0 month – 14 years old sickness rate is 9,3 (2011 y.) vs. 11, 1 (2013) cases for 100 k. children population. Annual risqué of children tuberculosis infection is 0,5 – 2,0 %. Analysis of unfavourable termination by tuberculosis of Donetsk region children let determinate that among dead children 80 % are unvaccinated children.